Year One of School Improvement: Examples from Nine Schools - Stephen P. Gordon; Suzanne Stiegelbauer; Julie Diehl (Educational Considerations, 2006)
School improvement research asks the question “How do schools improve over time?” and thus is focused on school culture and the change process.